The Impacts of Integrated Metallic Oxide Varistor (MOV)-Capacitor Banks on High Voltage AC Power Transmission System - Akinte, Oluwaseun Olanrewaju (Technium Electro, 2024)
To maximize the efficient utilization of HVAC (high voltage alternating current) system of power transmission in terms of power efficiency improvement, voltage support, sudden shift in loadings, occurrence of transient, power regeneration and regenerative braking currents (harmonics), the need for installation of integrated metallic oxide varistor-electrochemical capacitor banks is essential in electrical power systems because the application of electronic converters (rectifiers, inverters, bi-directional converters) are responsible for regenerative braking currents (harmonics) continuously. Hence the behavioural response from an external disturbance on electrical power system should be taken seriously into consideration if continuous effective power flow must be maintained under certain conditions within the integrated system. This paper presents a non-compensational and compensational three-phase HVAC power transmission system, its transient effects during asymmetric faults (line-ground, line-line). Investigation of integrated metallic oxide varistor (MOV)-series compensational (electrochemical capacitors) effect on HVAC power system was carried out showing the power flow analysis between the power generation source and the load demand containing the modelled non-series and series compensated HVAC power transmission system in response to its behaviour through the application of MATLAB, Simulink and Simscape power system tool software.